Influence of ground coal bottom ash with different grinding time as cement replacement material on the strength of concrete - Burhanudin, Mohd Khairy; Wan Ibrahim, Mohd Haziman; Mohd Sani, Mohd Syahrul Hisyam; Juki, Mohd Irwan; Jamaluddin, Norwati; Putra Jaya, Ramadhansyah; Shahidan, Shahiron; Basirun, Nurul Fasihah; Mohd Bosro, Mohamad Zulhairi (Construction Research Institute of Malaysia (CREAM), 2018)
This study was conducted to determine the strength of concrete containing coal bottom ash (CBA) as cement replacement material. The original CBA were sieved passing 150 um sieve size then ground for 20, 30, and 40 hours using ball mill machine. The normal concrete were designed for grade 30 based on Department of Environmental method (DOE). The concrete were produced by replacement level of cement 10%, 20% and 30%. The fresh concrete were tested using slump cone to determine the workability of concrete. It is found that slump height was decrease with increasing the replacement level of CBA. The concrete cubical with size 100 × 100 × 100 mm were prepared and tested to determine the compressive strength. It is shown that, the 20% replacement level of cement with 30 hours grinding time contributed high compressive strength compared to others. The presence of CBA in cement as a binder was improves the strength of concrete. It can be concluding that, CBA can be used as cement replacement material by appropriate replacement level.